2016
DOI: 10.1073/pnas.1522670113
|View full text |Cite
|
Sign up to set email alerts
|

Globin X is a six-coordinate globin that reduces nitrite to nitric oxide in fish red blood cells

Abstract: The discovery of novel globins in diverse organisms has stimulated intense interest in their evolved function, beyond oxygen binding. Globin X (GbX) is a protein found in fish, amphibians, and reptiles that diverged from a common ancestor of mammalian hemoglobins and myoglobins. Like mammalian neuroglobin, GbX was first designated as a neuronal globin in fish and exhibits six-coordinate heme geometry, suggesting a role in intracellular electron transfer reactions rather than oxygen binding. Here, we report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…Zebrafish globin X and human Ngb were expressed in the same fashion as Cygb1, as described previously 20, 26 . GbX incorporated an N-terminal His tag, and was purified by Ni-NTA agarose chromatography as described above for the Cygb proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Zebrafish globin X and human Ngb were expressed in the same fashion as Cygb1, as described previously 20, 26 . GbX incorporated an N-terminal His tag, and was purified by Ni-NTA agarose chromatography as described above for the Cygb proteins.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, multiple additional family members have been characterized that, similar to Mb, are classically considered “nonblood” or “tissue-expressed” globins [although, see Götting and Nikinmaa (2015), Corti et al. (2016a,b)], namely, neuroglobin (Ngb) (Burmester et al. 2000), cytoglobin (Cygb) (Kawada et al.…”
Section: Introductionmentioning
confidence: 99%
“…5, 6 The latter hypothesis has been supported by experimental data showing that other globins signal via nitrite reduction, including myoglobin, cytoglobin, neuroglobin and globin X. 79 This signaling has been shown to modulate hypoxic vasodilation, platelet activation, and mitochondrial respiration (recent platelet inhibition studies summarized 10 ). Both models propose allosteric-coupled hemoglobin deoxygenation and NO delivery and both models have central mechanisms that are testable.…”
mentioning
confidence: 92%
“…5, 12 Recent studies that other globins exhibit nitrite-reductase signaling activity, confirmed with genetic knock-down approaches, provides more direct evidence in support of this hypothesis. 79 …”
mentioning
confidence: 99%